(untitled) (Baghdad Science Journal, 2020)
The effects of temperature on an exotic aquatic snail Pomacea canaliculata (Lamarck, 1819) collected from the Shatt Al-Arab intertidal zone were investigated. A series of laboratory experiments were conducted during the summer period of 2017. Individuals of new born snails hatched in the laboratory from adult snails were collected from Shatt Al-Arab intertidal zone, and subjected to five fixed temperatures: 15, 25, 35, 40 and 45 Cº, after short term thermal acclimation. The heartbeats (HB) were counted at each temperature level. The results showed significant direct increase of HB from 15 Cº (19.8 HB/min) up to 25 Cº (76 HB/min) (P<0.05) as well as from 25 Cº to 35 Cº (93 HB/min). At 40 Cº the snail HB shows only slight insignificant increase (79 HB/ min). At 45 ºC the HB became irregular and showed negative thermo cardiac activity (HB dropped to 50.4/min). The minimum HB rate of 11/min was recorded at 15 Cº and the maximum value of 119 HB/min was recorded at 40 Cº. The study concluded that P. canaliculata can be highly stressed when exposed to extreme temperature experienced during the prolonged summer months and will no longer tolerate living in the intertidal zone of Shatt Al-Arab.